Physiological, perceptual and performance variables partially predict pacing in judo - Franchini, E.; Takito, M. Y.; Julio, U. F. (International Journal of Performance Analysis in Sport, 2023)
This study was conducted to estimate the main actions during a judo match based on athletes` physical fitness. Forty-one male adult judo athletes (23.3 ± 5.8 years old; 78.9 ± 11.6 kg; 174.7 ± 5.9 cm) underwent anthropometric measurements and a test battery to evaluate lower- and upper-body aerobic and anaerobic power and capacity, upper-body dynamic strength-endurance and performed one 5-min match simulation. The time-motion variables were recorded and used to determine the athletes` pacing. Perceptual, physiological, and performance variables were used to estimate the actions during the match via multiple regression analysis. The association between the frequency of attacks and upper-body strength-endurance confirmed the relevance of developing this capacity for high-intensity actions during the match. Aerobic capacity and power were related to high-intensity actions during the match. Anaerobic power and aerobic capacity were negatively related to high-intensity strength-endurance actions across the match (grip time), while upper-body VO2peak positively influenced it. Groundwork time was determined by aerobic capacity, upper-body strength-endurance, and anaerobic power. However, the coefficient of determination for these relationships was low to moderate (i.e. 0.13-0.51). Thus, different combinations of physiological, perceptual, and performance variables could partially estimate frequency and time of high- and low-intensity actions during the match.